Controlling Molecular Motion, Assembly and Coupling as a Step towards Molecular Actuators. - Murphy, Colin. (2017)
Abstract: In order to incorporate molecules as actuators in synthetic molecular machines, methods must be developed to drive the motion of individual molecules using external energy sources and to couple the motion of these molecules to other agents. Therefore, this dissertation will first focus on the production of multiple surface-bound molecular devices that function through the same mechanism, and subsequently investigate the intermolecular interactions of surface bound molecules. Chapter 2 outlines the flashing temperature-like ratchet mechanism by which the molecular machines are coupled to electrical energy. In Chapter 3, copper atoms from a surface are incorporated into Ullman-coupling intermediate based molecular rotors, producing one of the few reported altitudinal surface-bound molecular rotor. Chapter 4 deals with directing the diffusion of molecules across metal surfaces. In Chapter 5, dithiaethers are examined as molecular walkers and the impact of chain flexibility and binding site preference on their diffusion is investigated. The coupling of molecules requires intermolecular interactions and ideally, these connections should be spatially resolved, directable and reversible. Therefore, the second section of the dissertation examines how intermolecular interactions are modified by chemical and surface changes. Chapters 6 and 7 examine 1,2-dihydro-1,2-azaborine, a carbon-boron-nitrogen heterocyclic compound that is isoelectronic to benzene. Interestingly, the incorporation of the B-N unit produces a molecular dipole and has the potential to form dihydrogen bonds. Therefore, chapter 6 quantifies the impact of these additional intermolecular interactions by comparing desorption of 1,2-dihydro-1,2-azaborine and benzene from identical surfaces. Chapter 7 examines how intermolecular interactions drive the formation of 1,2-dihydro-1,2-azaborine magic clusters on two metal surfaces. Next, chapter 8 examines how subtle variations in molecular geometry lead to drastic changes in the supramolecular self-assembly of thioethers. Chapter 9 details how the ordering and length of surface-bound hydrogen-bonded chains of methanol are dictated by the underlying surface and examines an unreported chiral meta-stable methanol hexamer. Single-molecule measurements can answer many of the current questions in the field of molecular machines and lead to control of molecular motion. Development of mechanisms to direct molecular motion and to couple this motion to external systems is crucial for the rational design of new molecular machinery with functionalities such as mass transport, propulsion, separations, sensing, signaling and chemical reactions.; Thesis (Ph.D.)--Tufts University, 2015.; Submitted to the Dept. of Chemistry.; Advisor: Charles Sykes.; Committee: Elena Rybak-Akimova, Samuel Thomas, and Ivan Aprahamian.; Keywords: Chemistry, Nanotechnology, and Physical chemistry.